A Design Study of a Low-Cost Heterogeneous Parallel Computer - Barata, Jorge M M (2021)
A design study of a low-cost heterogeneous parallel computer based on already existing hardware is presented. The UNIX operating system is used together with PVM for message passing control. The parallel machine is constructed using existing Intel PC's and Alpha workstation platforms. The new techniques and algorithms are successfully applied to the grid generation problem based on the solution of partial differential equations with control of the boundary point distribution. Two different programming models were used. One uses decomposition of the domain into as many parts as there are processors, and revealed high reductions on the total turnaround time, although load balancing was a major problem. The other programming model has the possibility of changing the position of the points of the interface between each sub-grid, and allows reductions of the total turnaround time up to 1.6 times for the case of 3 processors, while the quality characteristics of the final grid are maintained. The communication times were reduced up to 7.5% of the total turnaround times, but the recursive nature of the numerical iterative process of the grid generation method causes a substantial increase in the number of iterations, reducing the parallel machine performance.